Does Hypochlorous Acid Cause Ototoxicity? An Experimental Study. Issue 10 (December 2022) - Mutlu, Ahmet; Gunduz, Ayşe Yasemin; Bakici Balci, Burcu; Erinc, Murat; Bulut, Erdogan; Ersoy, Onur; Kalcioglu, Mahmut Tayyar
Abstract : Aim: Hypochlorous acid (HOCl) is a weak acid that ionizes in water. It is an effective antiseptic exhibiting low toxicity on living tissues. We aimed to investigate the ototoxic effects of HOCl on an animal model by using electrophysiological and histological methods. Materials and Methods: The study comprised 32 Sprague-Dawley rats, which were separated into four groups: control group (A), saline solution group (B), 70% isopropyl alcohol + 2% chlorhexidine group (C), and HOCl group (D). After recording the auditory brainstem response (ABR) for basal hearing thresholds (8, 16, 24, and 32 kHz), 0.03 ml of the aforementioned materials was injected intratympanically three times every 2 days in groups B, C, and D. ABR measurements were repeated on the 7th and 21st days. All animals were sacrificed, and temporal bones were prepared for examinations of cochlear histology and vascular endothelial growth factor immunohistochemistry. Results: Basal hearing levels were normal across all frequencies and groups, with no statistical differentiation. On the 7th and 21st days after the ABR test, all other groups demonstrated a significant deterioration in hearing levels compared with group A. When the results from 7th and 21st days were compared within group D, a partial recovery was observed. In histopathology, groups C and D demonstrated moderate and severe cochlear degeneration, along with decreased immunoreactivity in the organ of Corti, stria vascularis, and spiral ligament. Conclusion: This is the first study to evaluate the safety of using HOCl in otology. Although HOCI is less ototoxic than the disinfectant used, it may have a toxic effect on cochlea. Level of Evidence: Animal Research.